Correction: Cardiac metastasis in papillary thyroid carcinoma: a case report and literature review - Zhang, Xiaonuo; Huang, Xinyu (Frontiers in oncology, 2025)
[This corrects the article DOI: 10.3389/fonc.2025.1590186.].